Sosialisasi dan Penyuluhan Undang-Undang Nomor 21 Tahun 2007 Tentang Pemberantasan Tindak Pidana Perdagangan Orang di Desa Lebak Kepuh Kecamatan Lebak Wangi sebagai Kantung Tenaga Kerja Wanita di Kabupaten Serang - Riswanda; Rahmawati Allyreza (BANTENESE : JURNAL PENGABDIAN MASYARAKAT, 2020)
Becoming a female worker abroad, especially in Middle Eastern countries, Malaysia is the dream and hope for most women and families in Lebak Kepuh Village. Family poverty factor is the main reason for families to send their children to work abroad. Working as farm laborers and getting caught up in loan sharks forced these families to send their children to become TKW. Private Indonesian Employment Service Delivery Companies (PPTKIS) have sprung up as a connector between workers and overseas job providers. However, unfortunately, many of these PPTKIS are not registered with the Ministry of Manpower and some are looking to the villages to seduce women to be sent to work abroad or in the capital city with the lure of a large salary. Even though this is often not true. Instead of getting a job, they are even traded in the trafficking of people into commercial sex workers and / or into illegal labor. This activity aims to socialize Law Number 21 of 2017 concerning the Eradication of the Crime of Trafficking in Persons. The causes, methods, methods and consequences of victims of trafficking in persons are presented and described in this activity. This includes serious legal sanctions that will be imposed on parties who deliberately commit the criminal act of trafficking in persons. Village officials ranging from neighborhood units, neighborhood units to village officials are at the forefront of preventing criminal acts of trafficking in persons because the form of trafficking begins with manipulating population data for poor families who want to send their children to work in public families, reporting companies that supply illegal foreign workers to the authorities. is an effort to stop the criminal act of trafficking in persons (women) in Desa Lebak Kepuh , Kecamatan Lebak , Serang Regency.